Analysis of the dissolution of CH4/CO2-mixtures into liquid water and the subsequent hydrate formation via in situ raman spectroscopy - Li, Zheng; Holzammer, Christine; Braeuer, Andreas S. (Energies, 2020)
We report an experimental study for the investigation into the suitability of hydrate formation processes for the purification of methane (CH4) from carbon dioxide (CO2) at a sub-cooling temperature of 6 K and a pressure of 4 MPa. The experiments were conducted in a stirred batch reactor. Three different initial CH4/CO2 mixtures with methane fractions of 70.1 mol%, 50.3 mol%, and 28.5 mol% were tested. The separation efficiency was quantified by measuring in situ via Raman spectroscopy the ratios of CH4/CO2 in the gas mixture, the liquid water-rich phase before hydrate formation, and the solid hydrate phase after the onset of the hydrate formation. The results indicated that the main separation effect is obtained due to the preferential dissolution of CO2 into the liquid water-rich phase before the onset of the hydrate formation.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Carbon dioxide; Gas hydrates; In situ Raman spectroscopy; Methane; Molar ratio